Acute Liver Failure as the Leading Manifestation of Spontaneous Tumour Lysis Syndrome in a Patient with NonHodgkin Lymphoma: Do Current Diagnostic Criteria of Tumour Lysis Syndrome Need Re-Evaluation? - Janja Tarčuković; Lara Valenčić; Željka Polonijo; Ana Fućak; Boban Dangubić; Igor Grubješić (Case Reports in Critical Care)
Tumour lysis syndrome (TLS) is a group of pathophysiological processes caused by rapid degradation of tumour cells with subsequent release of intracellular contents into the extracellular space. It is characterized by the development of systemic metabolic disturbances with or without clinical manifestations. The process usually occurs in highly proliferative, large tumours after induction of cytotoxic therapy. Rarely, however, spontaneous TLS can develop, as well as signs of multiorgan failure triggered by an excessive metabolic load and sterile inflammation. The combination of the aforementioned is thus quite unique. Here, we present a 63-year-old male in which spontaneous TLS was accompanied with acute liver failure and delineated underlying nonHodgkin lymphoma. Initial laboratory findings included hyperkalaemia, hyperphosphataemia, hypocalcaemia, uraemia, and increased creatinine levels indicating the onset of TLS with acute kidney injury. Moreover, the patient showed signs of jaundice, coagulopathy, and hepatic encephalopathy. Development of TLS with multiorgan failure prompted rapid initiation of critical care management, including vigorous intravenous fluid therapy, allopurinol treatment, high flow continuous venovenous haemodiafiltration, and commencement of chemotherapy. The case highlights the possibility of TLS as a differential diagnosis in patients presenting with multiorgan failure and the importance of early detection of this potentially challenging and fatal diagnosis.